2022
DOI: 10.3389/fviro.2022.838234
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Timing to Viral Suppression in HIV-Infected Pregnant Women in the University of Zimbabwe Birth Cohort Study During the Era of Lifelong Antiretroviral Therapy (Option B+ Treatment Strategy)

Abstract: BackgroundAchieving and maintaining viral suppression (VS) in people living with HIV/AIDS on antiretroviral therapy (ART) remains a crucial clinical goal, more so in pregnancy to prevent mother-to-child-transmission (MTCT). There is a need to understand VS kinetics and barriers to achieving it in order to meet the target of eliminating HIV-MTCT by 2030.MethodsHIV-infected pregnant women ≥20 weeks of gestation with different durations of Tenofovir/Lamivudine/Efavirenz exposures seeking antenatal care services a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 48 publications
3
10
2
Order By: Relevance
“…Studies conducted in Uganda and Kenya found no association between the two ( 25 , 26 ). Even though studies conducted in Ghana and Zimbabwe found that longer duration was associated with higher levels of viral suppression, the cutoff duration points were 3 years and 4.5 months, respectively ( 27 , 28 ). From this, we can conclude that the cutoff duration points are inconsistent and there are no proper scientific explanations for the comparable durations.…”
Section: Discussionmentioning
confidence: 98%
“…Studies conducted in Uganda and Kenya found no association between the two ( 25 , 26 ). Even though studies conducted in Ghana and Zimbabwe found that longer duration was associated with higher levels of viral suppression, the cutoff duration points were 3 years and 4.5 months, respectively ( 27 , 28 ). From this, we can conclude that the cutoff duration points are inconsistent and there are no proper scientific explanations for the comparable durations.…”
Section: Discussionmentioning
confidence: 98%
“…To investigate the role of ART, we categorized use as >126 days or sub-optimum (≤126 days) by the time of delivery as previously described (6). Differences in the groups of women; non-transmitters versus transmitters after stratification by timing of MTCT: IU, IP, and PP, were tested by Kruskal-Wallis, c 2 , or Fishers exact tests, where appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Date for ART commencement, compliance, and HIV status disclosure were recorded in HIV-infected women. According to the Zimbabwean national guidelines, all HIV-infected women should be on lifelong ART, but in practice, pregnant women often do not receive a timely HIV diagnosis (6). By then in 2016, the current standard of care for all HIVinfected pregnant women for PMTCT of HIV consisted of (non-)NRTIs, TENOLAM-E (Tenofovir, Lamivudine and Efavirenz).…”
Section: Maternal Questionnaires Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported the effectiveness of using LTE, such as a study in India reported the efficacy of using LTE was 98.7% and without major side effects [22], also in Africa, the use of LTE for more than 126 days showed virus suppression at undetectable levels [23]. The efficacy of TLE can be evaluated from the change of CD4 T lymphocyte count during therapy.…”
Section: Introductionmentioning
confidence: 99%